The Role of Customer Knowledge Management on The SMEs Business Performance - Ardik Praharjo; Kardina Yudha Parwati (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
This study examines Customer Knowledge Management (CKM) on innovation capability and business performance in Micro, Small, and Medium Enterprises (UMKM) in Malang. CKM emerged as an important dan effective system to improve innovation capabilities and company performance. However, the role of CKM in innovation and company performance is not recognized well by the company. The research method used is a quantitative explanatory approach. Data collection was collected through a questionnaire distributed to owners or managers of small dan medium industries, especially in the culinary sector, the variety of processed chips, which is the main domain of UMKM Malang City. The data analysis technique used is Partial Least Square (PLS). This study shows that customer knowledge management has a significant effect on innovation capability dan business performance.